A cross-sectional study on anxiety and stress in pregnant women with chronic HBV infection in the People’s Republic of China - Zhou F (Neuropsychiatric Disease and Treatment, 2015)
Fen Zhou,1 Jianju Li,2 Keke Lin,1 Ping Ji,1 Yumei Sun1 1School of Nursing, Peking University, 2Infection Control Department, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China Purpose: To investigate the anxiety and pregnancy-associated stress of pregnant women with chronic hepatitis B virus (HBV) infection in the People’s Republic of China and analyze the relationship between anxiety and pregnancy-associated stress in the hope of finding ways to reduce the stress or improve the coping skills for these mothers-to-be during pregnancy. Methods: A cross-sectional study was conducted. One hundred and sixty chronic HBV-infected pregnant women (HBV group) and 160 healthy pregnant women (control group) selected from three Peking University-affiliated hospitals participated in the study, and completed the State-Trait Anxiety Inventory (STAI) and Pregnancy Stress Rating Scale (PSRS) survey. Results: The mean scores of STAI and PSRS for the HBV group were higher than for the control group. Factor 2 of PSRS (stress caused by worrying about mother and child’s health and safety) was the highest, and was significantly higher in the HBV group than in the control group. Correlation analysis showed STAI scores were significantly correlated with economic status and diagnosis, as well as the total score, factor 1 (stress about identifying with the role of mother), and factor 2 of PSRS, but not significantly correlated with factor 3 of PSRS (stress caused by the changes of body shape and physical activity). Conclusion: Pregnant women with chronic HBV infection experienced higher levels of anxiety and stress than healthy pregnant women. Their major stress came from concerns for the health and safety of the mother and the child. Keywords: anxiety, pregnancy-associated stress, chronic HBV infection, State-Trait Anxiety Inventory, Pregnancy Stress Rating Scale